Working the Hyphen From Below: The “Thick Decryption of Subtext” and the Micro-Politics of Knowledge Production - de Souza, Rebecca (Frontiers in Communication, 2019)
Engaging in reflexive analysis or “working the Self-Other hyphen” is central to establishing credibility in critical qualitative research methods today. However, while there is a robust literature on how to navigate the Self-Other hyphen, this tends to be written for white scholars going into communities of color. There is very little written by and for scholars of color going into the field to study whiteness. In this paper, I unravel the challenges and complexities of negotiating the Self-Other hyphen as a scholar of color. This manuscript is based solely on a secondary analysis of previously published data. I draw on examples from my own health communication research over the past decade in two different settings: HIV and AIDS in India and hunger and food insecurity in the United States. I use peer reviews and reactions from dominant actors in the academy to elucidate how orientalist and white racial frames impact the interpretive, analytical, and writing work of qualitative research. Highlighting the micro-politics of knowledge production, the paper argues that since power operates differently for Black and brown researchers in white spaces, considerations for working the hyphen must be dramatically altered. The paper offers suggestions for how researchers might maintain a critical, counterhegemonic presence in their research in the face of hegemonic responses.